Strategies For Enhancing Zakat Fundraising Through The Utilization Of Social Media And Digital Campaigns - Zulkifli Zulkifli (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
This study investigates strategies to enhance zakat fundraising through the utilization of social media and digital campaigns. An integrated approach is employed, focusing on data-driven personalization, engagement through interactivity, utilization of analytical tools, simplicity of messages, captivating narratives, responsiveness to changing trends, and integrated message dissemination. The introduction provides background on the context of zakat fundraising and the crucial role of zakat in social welfare. The problem statement highlights challenges in fundraising and the significance of effective strategies. The research objectives involve analyzing social media as a zakat fundraising tool and evaluating the effectiveness of digital campaigns. The research methodology includes a literature review and case studies. The research findings indicate that the integrated approach has a positive impact, with personalization and interactivity being key factors. Emphasis is placed on the necessity of responsiveness to trends and integrated message dissemination to enhance awareness and community participation in zakat fundraising.